PENGARUH PENYULUHAN DIGITAL TERHADAP PENINGKATAN PENGETAHUAN IBU TENTANG PENTINGNYA ASI EKSKLUSIF PADA IBU HAMIL DI PUSKESMAS NGRAMPAL - Hatta Novika, Revi Gama; Sutikno, Edy; Setiawan, Meidyan Thomas; Wulandari, Nur; Nugraheni, Ratih Mutiara; Victorin, Wendewina (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Exclusive breastfeeding during the first six months of life is a crucial intervention to support optimal infant growth and development, as well as to reduce infant morbidity and mortality. However, the coverage of exclusive breastfeeding in Indonesia has not yet reached the national target. One of the contributing factors is the lack of maternal knowledge regarding the importance of exclusive breastfeeding. With the advancement of technology, health education can now be delivered digitally, enabling wider and more effective outreach. This community service activity aimed to analyze the effect of digital counseling on improving pregnant women’s knowledge about exclusive breastfeeding in the working area of Puskesmas Ngrampal, Sragen Regency. The program involved 35 pregnant women from Bener, Kebonromo, and Gabus villages. The intervention was conducted through educational video sessions, with knowledge measured using pre-test and post-test questionnaires. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed an increase in the mean knowledge score from 7.89 (pre-test) to 8.54 (post-test). The Wilcoxon test revealed a significance value of p = 0.003 (< 0.05), indicating a statistically significant difference before and after the intervention. These findings suggest that digital counseling is effective in enhancing pregnant women’s knowledge about exclusive breastfeeding. This activity recommends that health workers intensify the use of digital media in health promotion and develop sustainable educational content to support exclusive breastfeeding programs.